Structure, IR and Raman spectra of the optically active quaternized ammonium salt – promising object for liquid crystal systems. Issue 1 (21st November 2022) - Pitsevich, G.; Doroshenko, I.; Shundalau, M.; Rutkovskaya, L.; Lugovski, A.; Gusakov, G.; Lapanik, V.
Abstract: Compound synthesized N-[4-((2R)-octan-2-yloxy)benzyl]-N, N-dimethyl-hexadecane-1-aminium tosylate, which is a promising candidate for use in liquid crystal compositions. The Raman spectrum of the synthesized sample was also recorded. The equilibrium configuration of the molecule (ion) was calculated by optimization for all geometric parameters at the level of the B3LYP/cc-pVTZ theory. In addition, the equilibrium configurations of three more stable conformers of the molecule were calculated. The relative energies of the four conformers, their dipole moments were determined, and their IR and Raman spectra were calculated. Comparison of the calculated and experimental vibrational spectra of the molecule made it possible to assign the absorption bands and Raman scattering lines to the vibrations of molecular fragments.